Kendali Kecepatan Motor Induksi Satu Fasa Pompa Submersible Menggunakan Fuzzy Logic - Suci Wulan Dari; Beni Satria; Ahmad Dani (Jurnal Nasional Teknologi Komputer, 2026)
This study develops and implements a Fuzzy Logic Controller (FLC) for speed control of single- phase induction motors in submersible pump applications, addressing the critical need for energy-efficient variable speed drives in domestic and small-scale agricultural water systems. Single-phase induction motors are widely used in submersible pumps due to their simplicity and cost-effectiveness, yet conventional constant-speed operation results in significant energy waste under varying load conditions. The research employs both simulation using MATLAB/Simulink and experimental validation with a 0.75 kW motor-pump prototype to evaluate FLC performance against conventional PID controllers. The FLC is designed with seven triangular membership functions for each input (speed error and error rate of change) and output (frequency change), implementing 49 fuzzy rules based on expert knowledge. Experimental results demonstrate that FLC achieves superior performance with 38.58% faster rise time, 40.64% shorter settling time, 61.89% lower overshoot, and 74.49% smaller steady-state error compared to PID across various setpoint speeds. Energy efficiency analysis reveals 12.98% energy savings at 25% load and consistent improvements across all operating conditions, with weighted average efficiency of 67.55% versus 62.70% for PID. The FLC also exhibits excellent robustness under parameter variations, maintaining acceptable performance even with 20% resistance increase and 10% voltage drop. Power quality metrics show 3.45% higher power factor and 27.06% lower current Total Harmonic Distortion. Implementation costs remain identical to PID systems, providing superior performance without additional hardware investment. This research contributes practical solutions for national energy efficiency programs, with potential aggregate savings of hundreds of GWh annually if